IMPROVING STUDENTS’ READING COMPREHENSION ACHIEVEMENT WITH PQRST - Welly Ardiansyah (HOLISTICS, 2009)
The aims of the research are to know: 1) differences of  reading comprehension achievement through PQRST, and 2) how big the influences of independent variables to dependent variable. Method used in the research is the non-equivalent control group design. The findings show that there is a significant difference in term of reading comprehension  achievement between experimental and control group. To know the differences of reading comprehension achievement  between experimental and control group, t-test is applied. To know how big the influences of independent variables to the dependent  variable, the two tailed regression analysis is used. The contributions of independent variables, t-test and group, ara significant (0.000), meanwhile the contribution of Gender variable is not significant (0.166) to dependent variable.